Analisis Kinerja Pelayanan Publik Berbasis Online Di Kota Bekasi Melalui Penggunaan Aplikasi E-Open Dan Website MPP - Bayu Setya Aji; Adin Dahuri (Jurnal Ilmu Administrasi Publik, 2025)
Performnace Analysis of Online-Based Public Service in Bekasi City Through The Use Of E-Open Application and MPP Website Adminitrative Sciences, STIAMI Insitute, Advisor.Drs Adin Dahuri,M.M. The E-Open Application and MPP Website In Bekasi City Are Facility and infrastructure developed for public service. The purposes of is research counducted by field surveys are to indentify issues in performance, service, or public opinions on online- Based Public Service in Bekasi City Through The Use Of E- Open Application and MPP Website in Bekasi City and to find out Whether or not innovation factors affect public interest in Bekasi City. In addition,it provides insight for future improvements in addressing public concerns in online service. The resuts of the research on these tools serve as aducational processes that are update annually in accordance with exiting policies and procedures. They are essential elements in serving the public to ensure publc satisfaction and to meet their needs, the providing convenience and effective and efficient impact.